Therapeutic Potential of Enoxaparin in Lichen Planus: Exploring Reasons for Inconsistent Reports - Patel, Rahul P.; Shastri, Madhur D.; Ming, Long Chiau; Zaidi, Syed Tabish R.; Peterson, Gregory M. (Frontiers in Pharmacology, 2018)
Lichen planus (LP) is an uncommon mucocutaneous inflammatory condition, that is immunologically-mediated, typically pruritic and often recurs. The currently advocated therapies are either not highly effective or associated with severe side effects. Enoxaparin, a widely used anticoagulant, is composed of both anticoagulant and non-anticoagulant fragments. Enoxaparin is reported to have anti-inflammatory properties and it was found to be effective in LP. However, the results from clinical studies have varied substantially and, therefore, the clinical role of enoxaparin in LP remains uncertain. This review focuses on potential reasons for the reported inconsistent outcomes, as well as proposing solutions; these include identifying batch-to-batch inconsistency in the composition of enoxaparin. The potential therapeutic value of enoxaparin in LP must be explored using well-designed clinical trials, combined with experimental studies that focus on identifying the anti-inflammatory fragments of enoxaparin and elucidating the mechanism of action of these non-anticoagulant fragments.